Morphological variability of permanent mandibular first premolar teeth in Manipuri population: An In vitro study - Takhellambam Devi Premlata; Shamurailatpam Priyadarshini; Amandeep Kaur; B S Deepak; Nandita Kshetrimayum; Ng Sanjeeta (Wolters Kluwer Medknow Publications, 2021)
Aim: To investigate anatomical and morphological variability of permanent mandibular first premolar teeth in the population of Manipur state of Indian subcontinent. Materials and Methods: Four hundred and eighty teeth from a pool of Manipuri population were studied for anatomical and morphological variability using staining and clearing technique. All samples were evaluated for the number of roots, root canals, root canal configuration, presence of lateral canals, intercanal communications, and apical deltas. Results: Single root with one canal was present in 81.25% (390/480) and single root with two canals in 18.75% (90/480) of samples. Root canal configuration according to Vertucci's classification was as follows: Type I (43.7%) followed by Type V (25%), Type VI (12.5%), and Type II, III, and VII (6.25%). Intercanal communications in the apical third were 12.5% (60/480) and 6.25% (30/480) in the middle third of the root. Occurrence of lateral canals in the apical third was 18.75% (90/480). Apical delta was found in 37.75% (180/480) of samples. Conclusion: The results of this study highlight the variability patterns of mandibular first premolar tooth existent in the population of the state of Manipur. Single-rooted teeth are most common with predominantly Vertucci's Type I root canal configuration and significant presence of lateral canals and apical ramifications. Clinical Significance: Sound knowledge of anatomy of the root canal and possible variations can contribute to a successful treatment outcome.